Zastosowanie rozkładu Pareto w kalkulacji składki reasekuracji nieproporcjonalnej - nadwyżki szkód - Wieteska, Stanisław (Application of the Pareto Distribution for the Calculation of Non-Proportional Excess of Loss Reinsurance Premium, 2006)
In insurance practice there exist catastrophic losses. One kind of security against it is reinsurance. The goal of the paper is to calculate reinsurer's premium for excess of loss contract. For this purpose the property of the Pareto distribution is applied. The author introduces the characteristics of the Pareto distribution and the method of parameters estimation. In the last part of the article the example of frequency calculation and the expected value of loss calculation was proposed for the purpose of the reinsurer's net premium settlement.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 166-177